NUMBER AS THE ESSENCE OF THINGS: PYTHAGOREAN PHILOSOPHY - Sadullaeva, Matluba (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article discusses how Pythagorean philosophy evolved from seeing numbers as the basis of everything to understanding them as essential principles shaping the universe. It emphasizes the practical and philosophical significance of numbers, exploring their role in various fields like math, science, and ethics. Pythagoreans viewed numbers not just as tools for counting but as fundamental aspects of existence itself. They focused on two key principles: unity (monad) and duality (duad), seeing them as foundational concepts in understanding both numbers and reality[23]. The text also compares Pythagorean ideas with those of later philosophers like Plato, Iamblichus and others. Overall, it explores the profound implications of seeing the world through the lens of numbers.